Anti-Parasite and Cytotoxic Activities of Chloro and Bromo L-Tyrosine Derivatives (2018)
ABSTRACT: A series of twenty-one L-tyrosine derivatives with modifications in the halogenation pattern of the aromatic ring and different degree of methylations on the amine and phenolic hydroxyl groups were synthesized. The structures of all the intermediates and target compounds were confirmed unambiguous by spectroscopy analysis. Additionally, all compounds were evaluated against Plasmodium falciparum and Leishmania panamensis parasites between 20-702 µg mL-1. The cytotoxic evaluation was done to determine the selectivity index for each compound. Six compounds had the lower EC50 (effective concentration 50) against L. panamensis. One of these compounds was the most active with an EC50 at 24.13 µg mL-1 (76.07 µM). All derivatives showed no significant activity against P. falciparum and no compound has in vitro antifungal activity at 500 µg mL-1.